Infection of Two Heterologous Mycoviruses Reduces the Virulence of Valsa mali, a Fungal Agent of Apple Valsa Canker Disease - Yang, Shian; Dai, Ruoyin; Salaipeth, Lakha; Huang, Lili; Liu, Jie; Andika, Ida Bagus; Sun, Liying (Frontiers in Microbiology, 2021)
Mycovirus infection has been widely shown to attenuate the virulence of phytopathogenic fungi. However, such an effect has not been demonstrated for Valsa mali, an agriculturally important fungus that causes Valsa canker disease in apple trees. In this study, two unrelated mycoviruses [Cryphonectria hypovirus 1 (CHV1, genus Hypovirus, single-stranded RNA) and Mycoreovirus 1 (MyRV1, genus Mycoreovirus, double-stranded RNA)] that originated from Cryphonectria parasitica (chestnut blight fungus) were introduced into V. mali via protoplast fusion. CHV1 and MyRV1 stably infected V. mali and caused a reduction in fungal vegetative growth and virulence. Co-infection of both viruses further reduced the virulence of V. mali but compromised the stability of CHV1 infection and horizontal transmission through hyphal anastomosis. Infections of MyRV1 and, to a lesser extent, CHV1 upregulated the transcript expression of RNA silencing-related genes in V. mali. The accumulation of CHV1 (but not MyRV1) was elevated by the knockdown of dcl2, a key gene of the RNA silencing pathway. Similarly, the accumulation of CHV1 and the efficiency of the horizontal transmission of CHV1 during co-infection was restored by the knockdown of dcl2. Thus, CHV1 and MyRV1 are potential biological control agents for Valsa canker disease. However, while co-infection of both viruses further reduces fungal virulence, it has a negative effect on the accumulation of CHV1 and the efficiency of the horizontal transmission of CHV1 due to the activation of antiviral RNA silencing by MyRV1.